Analisis Faktor Penghambat Implementasi Manajemen Puskesmas Sukaramai Kota Medan Tahun 2020 - Katarina Susi Kartika Simaremare (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
The Community Health Center of Sukaramai is one of 41 Community Health Centre in Medan and It is one of the outpatient Community Health Centers. The management of Community Health Centre will integrate all existing management in solving health priority problems in their working areas. The process and stages of Community Health Centre Management at Community Health Center of Sukaramai cannot be carried out effectively and efficiently, where the human resources (HR) are still lacking and performance achievements have not reach targets. This study aims to analyze the inhibiting factors in the implementation of the management of the Community Health Center in Medan with a qualitative research design with a phenomenological design. Informants in this study were 6 people. Data collection by in-depth interviews. Triangulation of the head of the Community Health Centre, the head of administration and the staff of Community Health Centre. This research was conducted at the Community Health Center of Sukaramai in Medan from March to April 2020. The results showed that the inhibiting factors in the implementation of the Community Health Center management were the availability of incomplete data, internal and external meetings that could not run effectively, supervision, control and performance evaluation were not carried out. Routinely, the lack of management openness in matters of funds, fund management is still not optimal, communication is not good and effective, lack of resources both human, physical and financial resources as well as a lack of employee understanding of Community Health Centre management. The Community Health Center Management of Sukaramai is expected to be able to carry out the management of Community Health Centre with maximum, fair and open. open.